Utilization of evoked vibrational signatures under ultrasound examination as a novel method of tissue classification - Baxton R. Chen (WFUMB Ultrasound Open)
Background: Ultrasound interpretation requires extensive training and can be subjective and inexact. We previously reported a novel method of identifying tissues by analyzing the evoked vibrational signatures based on inherent tissue structural integrity and density during ultrasound examination. We now demonstrate the evoked tissue vibrational signatures of different tissues. Results: During ultrasound examination, the evoked vibrational signatures are detected by a portable dynamic signal recorder and interpreted based on time, amplitude, dampening, and frequency on single or multiple degrees of freedom. Various organs and tissue types were examined using ultrasound and unique vibrational signatures were recorded and stored in a proprietary database. Representative signatures of liver, kidney, lungs, and muscles were demonstrated, and their vibration frequencies and amplitudes were compared. Conclusion: We developed a method of using vibrational signatures to identify tissues under ultrasound examination, and we now report the signatures of different tissue types.